CNO and pep solar neutrino measurements and perspectives in Borexino. Issue 1 (January 2016) - Davini, S; Agostini, M; Appel, S; Bellini, G; Benziger, J; Bick, D; Bonfini, G; Bravo, D; Caccianiga, B; Calaprice, F; Caminata, A; Cavalcante, P; et al.
Abstract: The detection of neutrinos emitted in the CNO reactions in the Sun is one of the ambitious goals of Borexino Phase-II. A measurement of CNO neutrinos would be a milestone in astrophysics, and would allow to solve serious issues in current solar models. A precise measurement of the rate of neutrinos from the pep reaction would allow to investigate neutrino oscillations in the MSW transition region. The pep and CNO solar neutrino physics, the measurement in Borexino Phase-I and the perspectives for the new phase are reviewed in this proceeding.